Educational Theory-Integrated Construction Industry Training: State-of-the-Art Review - Jadallah, Hazem; Friedland, Carol J.; Nahmens, Isabelina; Pecquet, Charles; Berryman, Charles; Zhu, Yimin (Frontiers in Built Environment, 2021)
Workforce training is needed throughout the construction industry to create and maintain competent workers; unfortunately, most construction training and education research focuses on university student education. Integrating education science theory and into construction training has the potential to improve industry training but the status of this integration has not been well articulated. To address this gap, this paper undertakes grounded-meta analysis to provide a state-of-the-art review of education theory-integrated construction training for current industry professionals. To measure the extent of educational theory integration, this paper identifies and summarizes studies that meet inclusion criteria, identifies the frequency of occurrence of Bloom’s Taxonomy verbs as a measure of student learning outcomes, and identifies and compares commonly used words within the identified construction training literature and foundational educational theory literature. The results reveal that, of the 15 construction training studies that met the inclusion criteria, two-thirds (2/3) focused on worker safety and only three studies (20%) targeted managers or designers. Fewer than 35% of terms that were identified as frequently used terms in the published construction training studies were categorized as educational. The results of this paper provide a baseline of education theory-integrated construction training research, from which gaps and best practices can be identified and implemented to improve construction industry training.